Vitamin A Concentration in Cord and Maternal Serum and its Effects on Birth Weight (Bangladesh Journal of Child Health, 2010)
Introduction: Birth weight is a reliable index of intra-uterine growth and a major factordetermining child survival, future physical growth and mental development.Objectives: The present study was designed to explore the association of maternalserum as well as cord serum vitamin A level with birth weight.Materials and Methods: This prospective randomized study was carried out in Maternityand Child Health Training Institute (MCHTI), Azimpur, Dhaka during the period fromJanuary to July, 2002 on 100 healthy pregnant mothers of 38-40 weeks of gestationand on 100 new born babies born to these mothers.Results: Mean birth weight was 2804 gm (±43.1) with a range of 1600-3900 gm. Cordserum vitamin A level was 583 (±1.73) μg/dl with a range of 4.9-102.04 μg/dl, whilematernal serum vitamin A level was 53.5μg/dl (±1.5) with a range of 17.2-89.2 μg/dl.Newborn having birth weight ≥ 2500gm was found to have higher level of maternalserum vitamin A than the newborn having weight